Studi Eksperimental Pengontrolan Air Conditioning System Dengan Fuzzy Logic Control - -, Sudirman; Wijaya Kusuma, I Gusti Bagus; Sucipta, Made (Jurnal Energi Dan Manufaktur, 2012)
Electrical energy available in Indonesia at this time is not yet sufficient for all existing activities, this can be proved byfrequent occurrence of blackouts in several areas in Indonesia. It is necessary for a saving in electrical energy consumptionin all sectors, it is one of the refrigeration system. Research was conducted by testing AC (3 HP / 3 phase) using 2 differentcontrol systems, namely conventional control and FLC. Testing is done by placing the indoor units in cold storage room.Each test performed with varying load in the test room, ie no light burden, lamp 1000 Watt, and lamp 2000 Watt. Testingusing a conventional control system set point temperature 26 ° C and 3 variations of the differential is 1 , 2 and 3 , the FLCusing the temperature setting point 26 ° C. From this research we can conclude that the application of FLC system produceselectric energy consumption of the lowest compared to conventional control in this case is the differential 1. FLC applicationof electrical energy consumption at load 1000 Watt lower 11% and the load 2000 Watt 4% lower compared withconventional control in diffrensial 1.
Keywords: refrigeration systems, conventional control, FLC